Control interno y su incidencia en la gestión contable-administrativa de agro-servicio comercial Arias, cantón El Empalme, año 2012 - Molina Vélez, Jimson Augusto (2015)
This research on internal control and its impact on accounting and administrative management of Agro - service commercial Arias, was conducted at El Empalme town, Guayas Province, in 2012. The research found mainly that most of the traditional internal control tools that apply to the protection of the assets of Agro – Service Commercial Arias '' Service '' (cash book / bank, general ledger, Inventory - kardex) also employs periodic reconciliations of subsidiary records with the respective control account of major general, accounting balances at the end of each accounting period, bank reconciliation and internal control over income / expenses. Furthermore, with regard to the effectiveness of the method used to evaluate the internal control system of accounting income, expenses and inventory , developing Agro - Commercial Service '' Arias” found that this has a degree of medium confidence and medium risk control according to the method COSO I (65.6% NC, and 34.4 RC). The objective of this investigation there tries to help which the entity comes to where it wants to go and to avoid dangers, surprises in the way, evaluate the risks and mitigate the impact; adopting immediately criteria of improvements to the administrative systems, system of internal control and any operative aspect of the entity in order that they transform in opportunities and strategies that they lead to the development, strengthening, integrity and managerial stability, across evaluation of the management and feedback in the inventor systems, centring on the basic activities that they realize, since on it they depend to be kept competitive